Peningkatan hasil belajar matematika menggunakan metode demonstrasi di kelas II SDN Karanganyar 1 Kabupaten Pasuruan - Lailiyah, Ruhimatul; Setyawan, Agung (ARKA INSTITUTE, 2022)
This class action research aims to improve the mathematics learning outcomes of second grade students of SDN Karanganyar I Pasuruan Regency using the demonstration method. This research was carried out in two cycles, in which one cycle was carried out for one day. In each cycle there are stages of planning, action, observation, and reflection. The subjects of this study were grade II students of SDN Karanganyar I, Kraton District, Pasuruan Regency, totaling 30 students with 17 female students and 13 male students, grade II teachers of SDN Karanganyar I, and the principal of SDN Karanganyar I. The data collection techniques used in this study were observation, interviews, tests, and documentation. In analyzing data, there are three activities, namely data reduction, data presentation, and conclusion drawing/verification. The results showed that in cycle I of the pre-test stage, only 11 students (37.93%) achieved mastery and 18 students (62.06%) did not. In cycle I post-test stage, those who reached completeness were 14 students (48.27%) and those who did not were 15 students (51.72%). In the second cycle stage, almost all students reached mastery, namely 28 students (96.55%) and there was only 1 student (3.44%) who did not complete. Based on the results of the study, this demonstration method can improve the achievement of student learning outcomes, as well as increase enthusiasm in the learning process. When students are enthusiastic and excited about what they are learning, their learning outcomes can also improve, and it is likely that they will also be enthusiastic in other subjects. For teachers and prospective teachers, the demonstration method is very suitable to be applied in the current 2013 curriculum.